Effects of the COVID-19 Pandemic and Telehealth on Antenatal Screening and Services, Including for Mental Health and Domestic Violence: An Australian Mixed-Methods Study - Henry, Amanda; Yang, Jennifer; Grattan, Sarah; Roberts, Lynne; Lainchbury, Anne; Shanthosh, Janani; Cullen, Patricia; Everitt, Louise (Frontiers in Global Women's Health, 2022)
Introduction: Australian antenatal care includes specific screening and service provision for domestic and family violence (DFV), and mental health. However, the COVID-19 pandemic resulted in major care changes, including greatly expanded telehealth. Given difficulties in safe DFV and mental health assessment and management via telehealth, these services might be substantially impacted. This study aimed to assess COVID-19 effects on DFV and mental health pregnancy services as well as broader service provision from the perspective of local maternity service providers. Methods: Mixed-methods study of staff surveys and interviews in three Sydney (Australia) maternity units, October 2020-March 2021. Surveys and interviews interrogated perceived pandemic effects on delivery (ensuring required services occurred), timeliness and quality of (a) overall maternity care (b) DFV and mental health screening and care; and also advantages and disadvantages of telehealth. Surveys were descriptively analyzed. Interviews were conducted online, recorded and transcribed verbatim prior to thematic analysis. Results: Seventeen interviews were conducted and 109 surveys (67% midwives, 21% doctors, 10% allied health) received. Over half of survey respondents felt the pandemic had a negative effect on delivery, timeliness and quality of overall pregnancy care, and DFV and mental health screening and management. Perceived telehealth positives included convenience for women (73%) and reducing women’s travel times (69%). Negative features included no physical examination (90%), difficulty regarding non-verbal cues (84%), difficulty if interpreter required (71%), and unsure if safe to ask some questions (62%). Fifty-six percent felt telehealth should continue post-pandemic, but for <25% of visits. Those perceived suitable for telehealth were low-risk and multiparous women, while those unsuited were high-risk pregnancy, non-English speaking, and/or mental health/psychosocial/DFV concerns. “Change to delivery of care” was the central interview theme, with subthemes of impact on mental health/DFV screening, telehealth (both positive and negative), staff impact (e.g. continuity of care disruption), and perceived impact on women and partners. Discussion: While telehealth may have an ongoing, post-pandemic role in Australian maternity care, staff believe this should be limited in scope, mostly for low-risk pregnancies. Women high-risk due to physical health or mental health, DFV, and/or other social concerns, were considered unsuited to telehealth.